Arsenic ion Detection via Electron Chemical Reaction Mechanism Based on Interdigitated Electrode (IDE). (December 2018) - Mosbah, Ammar B.; Adam, Tijjani; Mohammed, Mohammed; Dahham, Omar S; Hashim, U.; Noriman, Nik Z.
Abstract: In recent days, both raw and treated water being consumed by human and animal posed serious threat to the consumer. Due to heavy industrialization water easily carries heavy metals that are harmful to consumers. Heavy metal is from metal or metalloid which found in environmental surroundings that has its potential toxicity. Most case, it is taken undetected due to absences of able sensor to detect it. Thus, this study posed to design and characterize nano interdigitated electrode (Nano-IDE) surface modified using Mercaptopropyltriethoxy silane (MPTES) to create binding chemistry for the enhancement of electrochemical activities that will allow specific and selective detection of arsenic ions in water. This result of the study has shown the potential of the proposed device.